The Influence of Information Susceptibility and Normative Susceptibility on Counterfeit Manufacturing Products Purchase Intention - Jati Kasuma Ali; Norlina Mohamed Noor; Abang Abdurahman; Anusara Sawangchai; Mohd Azizee Jemari (International Journal of Supply Chain Management, 2020)
Counterfeiting products trend of production, distribution and consumption is rising at an alarming rate. In Malaysia, counterfeiting has a market value worth $772.5 million and Malaysia is ranked number 40 in the world. For counterfeiters doing counterfeiting activities might ease their marketing strategy because they can easily join the popularity of the genuine branded goods. However, for genuine entrepreneurs, makers, and designers, the effects of counterfeiting resulted in loss of goodwill, damaging the brand’s reputation, equity and trust in the company. The objective of this study is to observe the influence of two social factors including informative and normative susceptibility which is related to consumers’ attitude and consumers’ purchasing intention of counterfeit products. The foundation of the variables for this study was assessed by using a validated online survey questionnaire through convenience sampling with a total of 207 respondents involved. The result indicated that informative susceptibility has negative, but significant relationship towards purchase intention of buying counterfeit products. It has proved that the more information the consumers get on the counterfeit products the lesser their purchase intention. However, subjective susceptibility has no relationship with intention to purchase counterfeit products. Future research directions and recommendations were also discussed in this research.